SCHEDULING SYSTEMS MAKE TO STOCK TO OPTIMIZING THE PRODUCTIVITY PROJECT PLANNER AT PT. GUNANUSA FABRICATORS - Khaeruman, Khaeruman; Kartawidjaja, Maria Angela; Sukwadi, Ronald (Yayasan Education and Social Center, 2024)
This research evaluates the effectiveness of the Make-to-stock scheduling system at PT. Gunanusa Utama Fabricators to optimize project planner productivity. The methods used include interviews, direct observation, and analysis of historical production data. The results show that implementing the Make-to-stock system increases production efficiency by maintaining stock that is ready to sell before demand arises. Challenges mainly relate to efficient stock management and complex production scheduling. This research highlights the importance of the role of project planners in facing a rapidly changing industrial environment and the comparison between manual and automatic scheduling. The implications are relevant for manufacturing companies in improving their operational performance by selecting scheduling methods that suit their unique context and characteristics